Sickle cell disease and the family: a phenomenological study - Garrett, Kevin C. (Kansas State University, 2014)
Sickle cell disease (SCD) is a prevalent, pervasive chronic illness. It is a hereditary condition that affects those of African, Mediterranean, Indian, Middle Eastern, and Hispanic/Latino descent. It causes extreme pain for patients and a myriad of other symptoms and complications. The medical issues associated with and the very nature of SCD has the potential to cause psychological distress and related problems for patients. Parents, caregivers, significant others, and family members are similarly affected by a family member with SCD. Applying the Vulnerability-Stress-Adaptation Model, this qualitative study used heterogeneous sampling and explored the experience of three families with SCD. Three main themes emerged from the data, analyzed using thematic analysis: Stress and Challenges, Adapting to and Coping with the Demands of SCD, and Individual and Family Strengths. The pervasiveness and unpredictability of SCD as well as the strengthening effects of having experienced SCD were shared across families, despite their heterogeneity. Clinical implications for families with SCD are discussed.
Keywords: Sickle cell disease; Psychological distress; Family; Qualitative study; Psychosocial problems; Coping and adaptation; Behavioral Sciences (0602); Mental Health (0347); Psychology (0621)